The role of ACE1 I/D and ACE2 polymorphism in the outcome of Iranian COVID-19 patients: A case-control study - Faridzadeh, Arezoo; Mahmoudi, Mahmoud; Ghaffarpour, Sara; Zamani, Mohammad Saber; Hoseinzadeh, Akram; Naghizadeh, Mohammad Mehdi; Ghazanfari, Tooba (Frontiers in Genetics, 2022)
Background: Since the beginning of the pandemic of coronavirus disease 2019 (COVID-19), many countries have experienced a considerable number of COVID-19 cases and deaths. The etiology of a broad spectrum of symptoms is still debated. Host genetic variants might also significantly influence the outcome of the disease. This study aimed to evaluate the association of angiotensin-converting enzyme (ACE1) gene Insertion/Deletion (I/D) polymorphism (rs1799752) and ACE2 gene rs1978124 single nucleotide polymorphism (SNP) with the COVID-19 severity. Methods: This study was conducted on 470 COVID-19 patients and a control group of 56 healthy individuals across several major cities in Iran. The blood sample and clinical data were collected from the participants, and their ACE1 I/D and ACE2 rs1978124 polymorphisms were determined using PCR and PCR-RFLP, respectively. Serum levels of C-reactive protein (CRP), interleukin 6 (IL-6), and ACE1 were measured in the blood samples. Results: We found that the ACE1 DD genotype frequency was inversely correlated with the risk of intubation (P = 0.017) and mortality in COVID-19 patients (P = 0.049). Even after adjustment, logistic regression demonstrated that this significant inverse association remained constant for the above variables at odds ratios of (OR) = 0.35 and OR = 0.49, respectively. Also, in the expired (P = 0.042) and intubated (P = 0.048) groups with II + ID genotypes, the mean level of CRP was significantly higher than in the DD genotype group. Furthermore, in both intubated and expired groups, the mean serum level of ACE1 was higher compared with non-intubated and survived groups with II or II + ID genotypes. The results also indicated that ACE2 rs1978124 TT + CT genotypes in females have a significant positive role in susceptibility to COVID-19; however, in females, the TT + CT genotypes had a protective effect (OR = 0.098) against the severity of COVID-19. Conclusion: These findings suggest that ACE1 I/D and ACE2 rs1978124 polymorphism could potentially influence the outcome of COVID-19 in the Iranian population.